ANALISIS PENGEMBANGAN PARIWISATA BERBASIS MASYARAKAT DI KAWASAN EKONOMI KHUSUS KABUPATEN LOMBOK TENGAH, NUSA TENGGARA BARAT - Dewi Cahyani, Putu; Urmila Dewi, Made Heny (E-Jurnal Ekonomi dan Bisnis Universitas Udayana, 2024)
The purpose of this study is to find (1) the influence of the role of government, social capital on community participation in the Mandalika special economic zone, (2) the influence of the role of government, social capital and community participation on the welfare of the community in the Mandalika special economic zone (3) community participation mediate the role of government and social capital on the welfare of the people in the Mandalika special economic zone. Data collection techniques were carried out by observation, interviews, in-depth interviews. Data were collected using a Likert scale, then analyzed using SEM-PLS. This study is a study using a sample of 300 respondents. This research is an associative research that uses primary and secondary data. The results showed that the role of government and social capital had a positive and significant effect on community participation, then the community participation variable had a positive and significant effect on community welfare and community participation variables mediated the role of government and social capital on community welfare in the Mandalika special economic zone in Central Lombok Regency. West Nusa Tenggara.